Perlindungan Hukum Kesehatan Anak dalam Pusaran Kelalaian Program Makan Bergizi Gratis - Prameswara Winriadirahman (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
The Free Nutritious Meal (MBG) program launched in early 2025 aims to tackle stunting, but its implementation has been marred by mass poisoning incidents affecting thousands of children. This research aims to analyze the form of government civil liability and legal protection for child victims of poisoning from the perspective of positive law in Indonesia. Using a normative juridical research method, this study examines various regulations such as the Child Protection Law, Health Law, Food Law, and Supreme Court Regulations (PERMA). The results indicate that the government's failure to ensure food safety constitutes an Unlawful Act by the Authority (Onrechtmatige Overheidsdaad). Based on PERMA Number 2 of 2019, this dispute falls under the absolute competence of the Administrative Court (PTUN). Victims' families can demand material and immaterial compensation collectively through a class action mechanism according to PERMA Number 1 of 2002. Legal protection for children includes preventive aspects through strict supervision from production to distribution stages, as well as repressive aspects through medical rehabilitation and compensation. The success of the MBG program is measured not only by budget absorption but also by the realization of a safe and accountable child protection ecosystem.